The roots of Ukrainian nationalism : Galicia as Ukraine's Piedmont - Magocsi, Paul R. (CEL - Canadian Publishers Collection., 2002)
This study provides a solid background for understanding nineteenth-century Galicia as the historic Piedmont of the Ukrainian national revival.